Metastatic signet‐ring cell carcinoma of the testis: An unusual case report in Syria - Zein A. Alsayed‐Ahmad; Mohammed Mayo; Hassan Alshaker; Leen Jarjanazi; Zeina Zakkour; Rima Sanaa; Yara Bilal; Anwar Chammout (Clinical Case Reports, 2023)
Key Clinical Message The case of a 44‐year‐old male with signet‐ring cell adenocarcinoma metastasis in the testis emphasizes the significance of immunohistochemistry in identifying the primary site of metastatic tumors. Further research is needed to establish effective treatment strategies for rare malignancies like small intestine signet‐ring cell carcinoma. Early diagnosis and appropriate treatment are crucial for improved patient outcomes. Abstract Metastasis to the testes is a rare occurrence, and identifying the primary site of origin can pose a significant challenge. Signet‐ring cell carcinoma (SRCC) is an uncommon subtype of adenocarcinoma typically found in the stomach but can also occur in other organs. This case report presents a 44‐year‐old male with signet‐ring cell adenocarcinoma metastasis in the right testis. The patient's initial clinical manifestation was testicular painful swelling, and subsequent immunohistochemical analysis using CK7, CK20, and CDX2 markers suggested a gastrointestinal origin. Normal upper and lower endoscopies rise suspicion of a small intestinal origin. The rarity of SRCC of the small intestine and the lack of clinical trials make treatment decisions difficult. This case highlights the importance of immunohistochemistry in determining the primary site of metastatic tumors and underscores the need for further research to establish optimal treatment strategies for rare malignancies like SRCC of the small intestine. As early diagnosis and appropriate treatment are critical for better patient outcomes.